The bourgeois revolution : the political birth of capitalism / by George Plechanoff ; translated by Henry Kuhn - Plekhanov, Georgii Valentinovich (1856-1918) (New York Labor News; 93)
En la cub.:Socialist Labor Party | How the bourgeoisie remembers its own revolution -- The bourgeoisie, anarchism and socialism